Efektifitas OJK Dalam Penanganan Kasus Investasi Online Bodong Quotex Ditinjau Dari Hukum Investasi (Studi Kasus Platform Quotex) - Ketut Astawa; Imam Budi Santoso; Tri Setiady; Embang Herlambang; Alin Kosasih (Universitas Ekasakti, 2024)
In this case, Doni Salmanan was reported for the Quotex platform trading fraud case on february 3 2022. Doni Salmanan was reported to the Police Criminal Investigation Unit on suspicion of fraudulent investments. The report on Doni Salmanan is registered in the police report (LP) number LP: B/0059/II/2022/SPKT/BARESKRIM POLRI. LP was made on February 3 2022 by the reporter with the initials RA. The research uses a normative method which focuses on the study of legal principles. We focus on how the OJK institution monitors the implementation of P2P lending in Indonesia and analyzes legal problems, with the emergence of illegal P2P lending practices which are legally detrimental to consumers. From the analysis above, it can be concluded that the OJK's role in handling fraudulent investment cases in Indonesia has a significant influence, but there are several factors that can influence its effectiveness. The Quotex fraudulent investment case carried out by Doni Salmanan shows that state institutions that have the authority to supervise do not carry out their functions thoroughly, which has led to many fraudulent investment cases occurring in Indonesia. OJK must be able to carry out its role as a preventive measure for the many cases of fraudulent investment in Indonesia.